Detection of epithelial tumour RNA in the plasma of colon cancer patients is associated with advanced stages and circulating tumour cells. Issue 4 (1st April 2002) - Silva, J M; Rodriguez, R; Garcia, J M; Muñoz, C; Silva, J; Dominguez, G; Provencio, M; España, P; Bonilla, F
Abstract : Background: Although circulating tumour DNA has been detected in patients with different types of cancer, little is known of free RNA in cancer patients. Aims: We investigated the presence of RNA from epithelial tumours in plasma from patients with colorectal carcinomas, and its correlation with tumour characteristics and circulating tumour cells. Methods: β-actin mRNA was analysed to assess the viability of plasma RNA in samples from 53 patients with colonic cancer and 25 controls. Subsequently, nested primers were used to detect the presence of cytokeratin 19 (CK19) and carcinoembryonic antigen (CEA) RNA in the same samples. Nine clinicopathological parameters were studied to correlate the molecular and clinical parameters. Additionally, we investigated for micrometastases in blood in 18 of these patients and in 10 of the controls samples. Results: All samples had detectable quantities of β-actin RNA. In the controls, one case (4%) was positive for CEA and five (20%) for CK19 RNA; of the 53 patients, 17 cases (32%) were positive for CEA and 39 (73.6%) for CK19 RNA. This was statistically significant (p=0.000001). Advanced stages (p=0.03) and soluble CEA status (p=0.03) were associated with the presence of CEA, CK19, or both RNAs in plasma. Lymph node metastases (p=0.06) and vascular invasion (p=0.07) were almost significant. On the basis of these results, we examined the possible presence of micrometastases in blood in several of these patients. The presence of plasma tumour RNA was found to be associated with circulating tumour cells in blood (p=0.04). Conclusions: Epithelial tumour RNA is detectable in plasma from colon cancer patients. This molecular event is associated with advanced stages and circulating tumour cells. Our results could offer new approaches in the diagnosis and monitoring of colon cancer.